The Ratib saman: Tradition In Kerinci And Its Existence In The Modern Era - Fransiska, Olan; Hidayat, Taufiq; Ulumuddin, Ulumuddin (Contemporary Society and Politics Journal, 2022)
The purpose of this study is to introduce to the general public ratib saman, its origins, and pronunciations in the series of implementation of ratib saman. Because many of the kerinci people, exceedingly ordinary people, do not know ratib saman or even don't know what ratib is. Until now, many Kerinci people still do not know ratib saman. So some time ago, a video of the community doing this ratib saman tradition developed on social media, and many comments from ordinary people who did not know ratib saman thought this ratib saman was a cult. However, several areas in Kerinci are famous for their scholars who bring and practice this ratib saman and then introduce ratib saman to the people so that it becomes a tradition or local wisdom in their area. This ratib saman is a series of dhikr or praises to Allah subhanahu wa ta`ala. Ratib saman is a teaching from the Order of Samaniyah, which was brought from Medina, Saudi Arabia, by previous scholars who performed the pilgrimage and at the same time studied there. Then it was developed in the regions of Indonesia up to the Kerinci district. Saudi Arabia by previous scholars who performed the pilgrimage and at the same time studied there. Then it was developed in the regions of Indonesia up to the Kerinci district. Saudi Arabia by previous scholars who performed the pilgrimage and at the same time studied there. Then it was developed in the regions of Indonesia up to the Kerinci district.